The Activities of Local Government with Regard to Supporting Entrepreneurship in the Municipalities of Wielkopolska Province - Dropek , Kinga (Studia Oeconomica Posnaniensia, 2014)
There is no clear or universal interpretation of entrepreneurship, though a range of definitions and analyses of the concept exist. Representatives of many scientific disciplines have explored this multidimensional issue and therefore it is difficult to find a common position regarding the concept of entrepreneurship. Increasingly, rather than being restricted just to the business sector, entrepreneurship is also being applied to the public and the social sectors. In addition to classical business entrepreneurs, public, social, civic and even political entrepreneurs have also appeared. Entrepreneurship in relation to local government concerns primarily initiatives, often supplementing public or private initiatives, which aim to improve the standards of social welfare and, in an institutionally innovative way, fill unoccupied "niches" in respect of services and social projects. One of the tasks of local governments is the development of entrepreneurship and its support by means of the available instruments, and every local government has a wide range of instruments at their disposal for the promotion of entrepreneurship. The climate for entrepreneurship depends on almost every, even minor, decision by local governments and other institutions. In the literature, various classifications of instruments for promoting entrepreneurship can be found. Typically, however, they are divided into income instruments, which primarily include tax reductions and exemptions; and expenditure instruments, the most important one being capital expenditure. The study analyses empirical data collected from 68 municipalities in the Wielkopolska region.